Latinisms in the Texts of Lithuanian Tatars (Using the Example of Tefsir from Olita 1723) - Kozhinowa, Alla (Slavistica Vilnensis, 2025)
The article is devoted to the analysis of Latinisms in the tefsir from Olita, the Polish translation of the Koran, which, being made by the Tatars of the Grand Duchy of Lithuania, is the oldest translation of the holy book of Islam into the Slavic languages. Both direct borrowings and indirect ones, when there was another intermediary language between the donor language (Latin) and the recipient language (Polish), are considered. It was noted that the text contains the largest number of nouns of Latin origin, followed by verbs, and adjectives are few in number. The article concludes that the presence of Latinisms in the text of the translation indicates that the translators belonged to the culture of the Polish gentry, and number of Latinisms per unit of text (25 word usages out of 6000 word usages of the text, what, according to researchers, was characteristic of Polish literature in the 16th century) confirms the dating of the lost prototype of the tefsir to the end of the 16th century. The fact that the formal signs of some Latinisms indicate their penetration into the text of the translation through the East Slavic languages confirms the fact of its creation in the territory directly bordering on the territory of distribution of these languages.